Walt Whitman papers in the Charles E. Feinberg collection - Feinberg, Charles E., 1899-1988; Allen, Gay Wilson, 1903-1995.; Bucke, Richard Maurice, 1837-1902.; Feinberg, Charles E., 1899-1988.; Johnston, John, 1852-1927.; Miller, James E. (James Edwin), 1920-2010; O'Connor, William Douglas, 1832-1889.; Traubel, Anne Montgomerie, 1864-1954.; Traubel, Horace, 1858-1919.; Traubel, Horace, 1858-1919; Traubel, Horace, 1858-1919.; Whitman, Walt, 1819-1892.; et al.
Correspondence, literary manuscripts, diaries, commonplace books, notes, and other papers relating to Whitman's life and writings which were collected by Feinberg. Literary manuscripts include Leaves of Grass (1855), Drum Taps (1865), Democratic Vistas (1871), Specimen Days (1882-1883), and November Boughs (1888). Includes manuscripts and proofs of works about Whitman including Gay Wilson Allen's The Solitary Singer; a Critical Biography of Walt Whitman (1955), James E. Miller's A Critical Guide to Leaves of Grass (1957), and Horace Traubel's In Re Walt Whitman (1893) and With Walt Whitman in Camden (1906). Also includes papers, relating chiefly to Whitman, of the following individuals Richard Maurice Bucke, Charles E. Feinberg, John Johnston, William Douglas O'Connor, and Horace and Anne Montgomerie Traubel. Subjects include the Civil War in Washington, D.C., proceedings of the U. S. Congress, Armory Square Hospital, Washington, D.C., and Abraham Lincoln and his assassination. Includes a walking stick, haversack, spectacles, and other memorabilia.
Correspondents include Richard Maurice Bucke; John Burroughs; Edward Carpenter; Francis Pharcellus Church; William Conant Church; Moncure Daniel Conway; Mary Whitall Smith Costelloe; Thomas Donaldson; Edward Dowden; Peter Doyle; Charles W. Eldridge; Ralph Waldo Emerson; Hamlin Garland; Anne Burrows Gilchrist; Joseph Benson Gilder; Richard Watson Gilder; Ulysses S. Grant; Bret Harte; Robert Green Ingersoll; John Johnston; William Sloane Kennedy; Sidney H. Morse; Ellen M. O'Connor; William Douglas O'Connor; T.W. Rolleston; William Michael Rossetti; Bethuel Smith; Logan Pearsall Smith; Robert Pearsall Smith; J.M. Stoddart; Bram Stoker; John Addington Symonds; Alfred Tennyson, Baron Tennyson; Horace Traubel; J.W. Wallace; Oscar Wilde; Talcott Williams; and members of the Stafford family.
Microfilm edition of notebook (1857) available
Microfilm edition of index cards available
Microfilm edition of containers 1-52 available
Microfilm produced from originals in the Manuscript Division.
Library of Congress Rare Book and Special Collections Division.
Library of Congress Prints and Photographs Division.
Keywords: Bucke, Richard Maurice, -- 1837-1902 -- Correspondence; Burroughs, John, -- 1837-1921 -- Correspondence; Carpenter, Edward, -- 1844-1929 -- Correspondence; Church, Francis Pharcellus, -- 1839-1906 -- Correspondence; Church, William Conant, -- 1836-1917 -- Correspondence; Conway, Moncure Daniel, -- 1832-1907 -- Correspondence; Costelloe, Mary Whitall Smith -- Correspondence; Donaldson, Thomas, -- 1843-1898 -- Correspondence; Dowden, Edward, -- 1843-1913 -- Correspondence; Doyle, Peter, -- 1847- -- Correspondence; Eldridge, Charles W. -- Correspondence; Emerson, Ralph Waldo, -- 1803-1882 -- Correspondence; Garland, Hamlin, -- 1860-1940 -- Correspondence; Gilchrist, Anne Burrows, -- 1828-1885 -- Correspondence; Gilder, Joseph Benson, -- 1858-1936 -- Correspondence; Gilder, Richard Watson, -- 1844-1909 -- Correspondence; Grant, Ulysses S. -- 1822-1885 -- Correspondence; Harte, Bret, -- 1836-1902 -- Correspondence; Ingersoll, Robert Green, -- 1833-1899 -- Correspondence; Johnston, John, -- 1852-1927 -- Correspondence; Kennedy, William Sloane, -- 1850-1929 -- Correspondence; Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865 -- Assassination; Morse, Sidney H. -- Correspondence; O'Connor, Ellen M. -- Correspondence; O'Connor, William Douglas, -- 1832-1889 -- Correspondence; Rolleston, T. W. -- 1857-1920 -- Correspondence; Rossetti, William Michael, -- 1829-1919 -- Correspondence; Smith, Bethuel -- Correspondence; Smith, Logan Pearsall, -- 1865-1946 -- Correspondence; Smith, Robert Pearsall, -- 1827-1898 -- Correspondence; Stoddart, J. M. -- 1845-1921 -- Correspondence; Stoker, Bram, -- 1847-1912 -- Correspondence; Symonds, John Addington, -- 1840-1893 -- Correspondence; Tennyson, Alfred Tennyson, -- Baron, -- 1809-1892 -- Correspondence; Traubel, Horace, -- 1858-1919 -- Correspondence; Wallace, J. W. -- 1853-1926 -- Correspondence; Wilde, Oscar, -- 1854-1900 -- Correspondence; Williams, Talcott, -- 1849-1928 -- Correspondence; Stafford family -- Correspondence; Whitman family; Armory Square Hospital (Washington, D.C.); Charles E. Feinberg Collection of Walt Whitman (Library of Congress); American literature; American poetry; American prose literature; Poetry; United States -- Politics and government -- 1861-1865.; Washington (D.C.) -- History -- Civil War, 1861-1865.; Collectors